Preoperative abnormalities in serum sodium concentrations are associated with higher in-hospital mortality in patients undergoing major surgery. (January 2016) - Cecconi, M.; Hochrieser, H.; Chew, M.; Grocott, M.; Hoeft, A.; Hoste, A.; Jammer, I.; Posch, M.; Metnitz, P.; Pelosi, P.; Moreno, R.; Pearse, R.M.; et al.
Abstract: Background: Abnormal serum sodium concentrations are common in patients presenting for surgery. It remains unclear whether these abnormalities are independent risk factors for postoperative mortality. Methods: This is a secondary analysis of the European Surgical Outcome Study (EuSOS) that provided data describing 46 539 patients undergoing inpatient non-cardiac surgery. Patients were included in this study if they had a recorded value of preoperative serum sodium within the 28 days immediately before surgery. Data describing preoperative risk factors and serum sodium concentrations were analysed to investigate the relationship with in-hospital mortality using univariate and multivariate logistic regression techniques. Results: Of 35 816 (77.0%) patients from the EuSOS database, 21 943 (61.3%) had normal values of serum sodium (138–142 mmol litre −1 ) before surgery, 8538 (23.8%) had hyponatraemia (serum sodium ≤137 mmol litre −1 ) and 5335 (14.9%) had hypernatraemia (serum sodium ≥143 mmol litre −1 ). After adjustment for potential confounding factors, moderate to severe hypernatraemia (serum sodium concentration ≥150 mmol litre −1 ) was independently associated with mortality [odds ratio 3.4 (95% confidence interval 2.0–6.0), P <0.0001]. Hyponatraemia was not associated with mortality. Conclusions: Preoperative abnormalities in serum sodium concentrations are common, and hypernatraemia is associated with increased mortality after surgery. Abnormalities of serum sodium concentration may be an important biomarker of perioperative risk resulting from co-morbid disease.